2013
DOI: 10.1080/17470919.2013.807301
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of interpersonal trust in borderline personality disorder by intranasal oxytocin and childhood trauma

Abstract: Borderline personality disorder (BPD) is characterized by interpersonal difficulties, whereby patients are negatively biased concerning the evaluation of others' trustworthiness. Here, we examined the effect of oxytocin on interpersonal behavior of BPD patients in a trust game, emphasizing the assessment of facial attractiveness of the patients' counterparts in the game, and patients' history of childhood trauma. Thirteen BPD patients and thirteen healthy controls played a trust game after receiving oxytocin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 31 publications
3
67
0
1
Order By: Relevance
“…For example, Bartz et al (2011b) and Ebert et al (2013) found that the administration of intranasal oxytocin to participants with borderline personality disorder—characterized by emotional instability and impulsiveness—led to less trusting and cooperative behaviour (also see Simeon et al , 2011). Together with the present results, these findings may point to an inverted U-shape relationship between oxytocin and rigid rule following on the one hand, and extreme emotional stability and impulsiveness on the other.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bartz et al (2011b) and Ebert et al (2013) found that the administration of intranasal oxytocin to participants with borderline personality disorder—characterized by emotional instability and impulsiveness—led to less trusting and cooperative behaviour (also see Simeon et al , 2011). Together with the present results, these findings may point to an inverted U-shape relationship between oxytocin and rigid rule following on the one hand, and extreme emotional stability and impulsiveness on the other.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note however that more studies are needed to inform our understanding of the relationship between oxytocin levels and psychotic symptomatology, as well as on the effects of oxytocin on the development of trust in clinical samples. For example, current evidence on the therapeutic effects of oxytocin administration in the treatment of psychotic symptoms are mixed (Feifel et al, 2016; Lee et al, 2016) and although oxytocin administration is shown to facilitate trust and corporation in healthy samples, the opposite effect has been observed in some studies involving patients suffering from BPD (Bartz et al, 2011; Ebert et al, 2013). …”
Section: Neurobiological Trajectories Linking Attachment To Psychosismentioning
confidence: 99%
“…These inter-individual differences may be a product of the social stimuli salience effect of oxytocin: as individuals with borderline personality disorder have increased incidences of insecure attachments and negative expectations from social interaction, increased salience to such stimuli may promote defensive behaviors and distress. Supporting evidence for this hypothesis includes findings that oxytocin may be most deleterious in individuals with borderline personality disorder who are anxiously attached (72) or reporting a history of emotional neglect in childhood (73).…”
Section: Oxytocinmentioning
confidence: 96%